Positioning IKN Dalam Konstelasi Asia Pasifik Dari Prespektif Geopolitik - Endarwati, Maria Cristina; Safa’at, Rachmad; Wicaksono, Agus Dwi (Universitas Gadjah Mada, 2024)
This study emphasizes the importance of careful planning and effective implementation to achieve a balance between economic development and environmental sustainability. Careful planning and effective implementation will ensure that IKN can become a symbol of Indonesia's progress and innovation in the international arena, and drive inclusive and sustainable economic growth.This study explores Indonesia's geopolitical role in the development of the Capital City of the Archipelago (IKN) in the Asia Pacific region. This study uses a qualitative approach with PESTO analysis, triangulation analysis, and paradigm shift analysis to validate data obtained from various sources, such as national policies, economic reports from international institutions such as the World Bank and IMF, as well as academic research from institutions such as CSIS and LIPI. This analysis identifies that the development of IKN in East Kalimantan has great potential to improve Indonesia's geopolitical position in the Asia Pacific region. The successful development of IKN will change international perceptions of Indonesia, strengthen national resilience through an integrated approach that covers economic, social, and environmental aspects, and improve economic competitiveness through modern infrastructure and better connectivity. The development of IKN is also expected to encourage more equitable regional integration and reduce the development gap between the western and eastern regions of Indonesia. The results of this study show that the development of IKN is not just an infrastructure project, but also a geopolitical strategy that can strengthen Indonesia's position on the world stage, improve people's welfare, and ensure sustainable development for future generations.